Fixed point results in C*-algebra valued fuzzy metric space with applications to boundary value problem and control theory - Das, G.; Goswami, N.; Patir, B. (Karagandy University of the name of acad. E.A. Buketov, 2024)
In this paper, we derive some new fixed point results in C*-algebra valued fuzzy metric space with the help of subadditive altering distance function with respect to a t-norm. Our results generalize some existing fixed point results in the literature. A common fixed point result is also derived for a pair of mappings on complete C*-algebra valued fuzzy metric space. The results are supported by suitable examples along with the graphical emonstration of the used conditions. As application, we establish the solvability of a second order boundary value problem. Moreover, the results are also applied in control theory to study the possibility of optimally controlling the solution of an ordinary differential equation in dynamic programming.
In this paper, we derive some new fixed point results in C*-algebra valued fuzzy metric space with the help of subadditive altering distance function with respect to a t-norm. Our results generalize some existing fixed point results in the literature. A common fixed point result is also derived for a pair of mappings on complete C*-algebra valued fuzzy metric space. The results are supported by suitable examples along with the graphical demonstration of the used conditions. As application, we establish the solvability of a second order boundary value problem. Moreover, the results are also applied in control theory to study the possibility of optimally controlling the solution of an ordinary differential equation in dynamic programming.
Keywords: C*-algebra valued metric space; fuzzy metric space; fixed point; boundary value problem; control theory